Informasi Anatomi dan Dosis Radiasi pada MSCT Brain Pediatric Menggunakan Adaptive Statistical Iterative Reconstruction (ASiR)-V - Fitri Indraratma; Dartini Dartini; Agung Nugroho Setiawan (Poltekkes Kemenkes Semarang, 2023)
Background: Multislice CT Scan (MSCT) brain examination in pediatric cases should pay attention to the lowest possible dose but still provide optimal anatomical information. Pediatric has a higher risk of developing cancer compared to adults who receive the same dose. The purpose of this study is to obtain the optimal value of the use of the Adaptive Statistical Iterative Reconstruction (ASIR)-V technique with variations in tube current strength and Iterative Reconstruction value which is implemented in pediatric patients under the age of 5 (five) years. Methods: This research was experimental with brain image samples of pediatric patients at the Radiology Installation of RSUD dr. Moewardi Surakarta. The variations of the tube currents selected were 80, 100, and 165 mA with a combination of AR20, AR40, AR60, and AR80 variations. Anatomical information processed descriptively sourced from the assessment of 3 (three) radiologists who were experienced in assessing MSCT images. Meanwhile, the effect of tube current variation on radiation dose was tested using linear regression. Results: The results showed differences in anatomical information between the combinations of 165 mA-AR60 and 165 mA-AR80